The Quartan Malarial Nephrotic Syndrome - R. G. Hendrickse (Paediatrica Indonesiana, 1975)
The Nephrotic Syndrome as classically described is a disease of unknown aetiology with a peak incidence in the first three years of life, highly selective proteinuria, minimal histological changes in the kidney and usually responsive to steroid therapy. Studies in tropical Africa in recent years have revealed a high incidence of the nephrotic syndrome in childhood which shows many differences from the syndrome as described elsewhere. The vast majority of cases occur in association with P. malariae infection, the peak incidence occurs at 5 - 6 years of age, proteinuria is usually poorly selective, distinctive histological changes are found in the majority and response to steroids, and other forms of treatment, is in general poor.